What a trip! - Foster, Kelli C.; Erickson, Gina Clegg; Gifford, Kerri (Hauppauge, N.Y. : Barron's, 1994)
Bub and Chub take trips on their ships, in space and on the sea.
ages 4-7
Keywords: Ships -- Fiction; Animals -- Fiction; Stories in rhyme; Outer space -- Fiction